2016
DOI: 10.1063/1.4971782
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of the plasma radial uniformity in single and dual frequency capacitively coupled argon discharges

Abstract: In the current work, the radial plasma density has been measured by utilizing a floating double probe in single and dual frequency capacitively coupled argon discharges operated in a cylindrical reactor, aiming at a better understanding of electromagnetic effects and exploring a method of improving the radial uniformity. The experimental results indicate that for single-frequency plasma sustained at low pressure, the plasma density radial profile exhibits a parabolic distribution at 90 MHz, whereas at 180 MHz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Due to continuous growth in both the driving frequency and the wafer size, plasma non-uniformities caused by the standing wave effect have become a major challenge in the material etching and film deposition processes. To optimize the plasma uniformity, several methods have been put forward, such as the use of specially shaped electrodes, [163][164][165][166][167] phase-shift control, [168][169][170] the use of the dual-frequency or multi-frequency source, [133,138,139,171,172] discharge symmetry control, [173,174] etc.…”
Section: Methods To Optimize the Plasma Uniformitymentioning
confidence: 99%
See 2 more Smart Citations
“…Due to continuous growth in both the driving frequency and the wafer size, plasma non-uniformities caused by the standing wave effect have become a major challenge in the material etching and film deposition processes. To optimize the plasma uniformity, several methods have been put forward, such as the use of specially shaped electrodes, [163][164][165][166][167] phase-shift control, [168][169][170] the use of the dual-frequency or multi-frequency source, [133,138,139,171,172] discharge symmetry control, [173,174] etc.…”
Section: Methods To Optimize the Plasma Uniformitymentioning
confidence: 99%
“…[168][169][170] This is the so-called "phase-shift control" method. Besides, the dual-frequency [138,139,171,172] or multi-frequency [133] source can be used as an alternative way to optimize the plasma uniformity. By using a two-dimensional plasma model, Bera et al [171] found that the plasma distribution can be effectively controlled by mixing VHF source powers at 60 MHz and 180 MHz.…”
Section: Methods To Optimize the Plasma Uniformitymentioning
confidence: 99%
See 1 more Smart Citation
“…Various doping methods have been studied with a-IGZO. Argon plasma bombardment was used in self-aligned top-gated TFTs, and the fluorine plasma process exhibited stable electron doping in a-IGZO . However, since both plasma treatments etch a-IGZO, even a slight difference in plasma density may cause large nonuniformity in electrical properties and surface roughness. , Hydrogen doping in a-IGZO has been widely studied with various approaches: thermal annealing, plasma treatment, and diffusion from a hydrogen-rich layer. , Hydrogen passivates native defects in a-IGZO and increases the electron density; however, unstable bonding between hydrogen and a-IGZO elements, which results in temporal instability even at room temperature, is yet to be solved. …”
Section: Introductionmentioning
confidence: 99%
“…The wafer scale uniformity of plasma etching processes is crit ically important to semiconductor fabrication [1]. Techniques to address the uniformity of plasma properties, and in par ticular the uniformity of reactant fluxes to etching surfaces, continue to be a high priority [2][3][4]. As feature sizes and film thicknesses shrink, conventional techniques to obtain uniform reactant fluxes and etch rates are being challenged to meet process demands.…”
Section: Introductionmentioning
confidence: 99%